2000
DOI: 10.1106/cwfv-2mdm-yefw-v4fe
|View full text |Cite
|
Sign up to set email alerts
|

Cure Monitoring of Matrix Resin with High-Frequency Electromagnetic Wave Transmission Line

Abstract: A new monitoring method for the curing process of matrix resin is proposed. In this method, a high-frequency electromagnetic wave transmission line is constructed inside or on the surface of a material and changes in the characteristics of the line during the curing process are measured. The use of a high-frequency electromagnetic wave mainly aims at getting information on the position of the discontinuity or distribution of material properties, making use of its short wavelength. As the first step of the inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Then, the RI would have decreased with the progress of curing because the transmission decreased with time. This behavior in which the RI decreased with progress of curing is consistent with the results of a previous study on cure monitoring of the resin with conventional dielectric measurement [21]. The cured resin would have had an RI in a range of 1.5 to 1.6 because the transmission of cured resin (-31.1 dB) was within the range of -36.0 to -27.3 dB, the corresponding RIs of which were 1.5 and 1.6, respectively.…”
Section: Resultssupporting
confidence: 91%
“…Then, the RI would have decreased with the progress of curing because the transmission decreased with time. This behavior in which the RI decreased with progress of curing is consistent with the results of a previous study on cure monitoring of the resin with conventional dielectric measurement [21]. The cured resin would have had an RI in a range of 1.5 to 1.6 because the transmission of cured resin (-31.1 dB) was within the range of -36.0 to -27.3 dB, the corresponding RIs of which were 1.5 and 1.6, respectively.…”
Section: Resultssupporting
confidence: 91%
“…In the calculation of Eq. 4, we used e r =2.7 [10] and e g =7 based on the catalog. The calculated relative permittivity of the resin mixed with glass particles, which is averaged for the lower and upper values of Eq.…”
Section: Methodsmentioning
confidence: 99%
“…This signal is expected to provide local information on the properties of the material or structure. We have conducted experimental and theoretical studies on the frequency characteristics of reflectance from two types of model transmission lines filled with epoxy resin [10]. Following this, we demonstrated that clearer information on resin flow or discontinuities in the curing stage can be obtained by the time-domain response to a step input signal [11].…”
Section: Introductionmentioning
confidence: 99%
“…Other cure monitoring methods that do not use dielectric property changes have also been reported. Urabe et al presented a cure monitoring method with a high frequency electromagnetic wave transmission line [7]. They investigated applicability of the method by comparing experimental results with those of calculations.…”
Section: Introductionmentioning
confidence: 99%